CARDIOVASCULAR DISEASES AND REHABILITATION MEASURES FOR PATIENTS - Sharipova Sevinch Samievna; Kafieva Martaba Khushvaktovna; Yakhyaeva Khurshida Yakhyaevna (World Scientific Research Journal, 2025)
Annotation : The article examines key aspects of rehabilitation of patients with cardiovascular diseases, including the importance of a comprehensive approach to restoring patients' health. The main stages of rehabilitation are included, including medical, physical and psychological support. The methods of physical activity, diet therapy and psycho-emotional support that help improve the quality of life and reduce the risk of recurrent cardiovascular events are considered